PENGARUH FAMILY CONTROL, SIZE, SALES GROWTH, LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN SEKTOR KEUANGAN - Harijono, Evelina (Business Accounting Review, 2014)
This study aims to know the influence of family control, size, sales growth, leverage towards profitability and firm`s value. Samples were taken from 66 from financial companies, listed in Indonesia Stock Exchange, ranging from 2009-2011. The hypotheses were tested using multiple regression analysis. In this study, profitability was measured by ROA (Return On Asset), and firm`s value was measured by Tobin`s q. The result were family control had no influence to both of profitability and firm`s value. Size had positive and significant influence to both of profitability and firm`s value. Sales growth had positive and significant influence towards profitability, but sales growth had no influence on firm`s value. Leverage had negative and negative and significant influence towards profitability, but leverage had no influence on firm`s value.